Moral Development Strategy in Shaping Youth Character through Al-Qur'an - Marpuah, Siti (International Journal Corner of Educational Research, 2022)
Lately, the era of globalization has had a less positive impact on the current generation of teenagers, this can happen because of the ongoing degradation of moral decline in youth. This is due to the acquisition of less positive things from various factors. For example, the excessive use of technology so that technology spoils teenagers, the decline in the behaviour of teenagers in everyday life, both in the school environment, home, and society in general. To find out strategies in forming youth morale by collecting research results in journal articles. This is intended for the younger generation to improve themselves and prepare them to build the nation in the future. A systematic review was used in the ways in obtaining Islamic youth character. Various articles are accessed using the Google Scholar database, ScieneDirect, and many other article search engines. This research showed that the moral formation of adolescents is very important in shaping the personality of adolescents and is expected to be able to build a nation with moral values ​​that the Qur'an guides. Not only that, teenagers are also equipped with moral values ​​to carry out their future lives.